Satellite view of the Sahel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Remote sensing of the Sahelian environment, 128pp, jointly published by The Commision of the European Communities (DG VIII) and CTA ISBN 92 9081 072 6 available from CTA